Research on the strengthening of the leading role of the government in urban social pension institutions in Hebei Province - Zhang, Hanyue; Jiang, Jingyuan (International Journal of Global Economics and Management, 2024)
In 1999, China enters the aging society as a whole. How to deal with the aging crisis of Hebei Provincial government is facing a severe test. In recent years, the number of elderly people in the province has continued to rise, and by the end of 2022, the proportion of elderly people over 60 years old has reached 21.01%, and the pressure on social pension has been increasing. On the one hand, in today’s era, the family structure is generally small, young people work hard, the change of family mode has impacted the traditional way of providing for the elderly, and it is difficult to meet the growing and diversified needs of the elderly. On the other hand, the concept of old-age care has changed, and the development of The Times has given the elderly more choices to enjoy their later life. Based on this, institutional pension plays an irreplaceable role as an important way of providing for the elderly, and the way of providing for the elderly is no longer just fixed in the traditional home pension. By studying the leading role of the government in urban social pension institutions in Hebei province, this paper finds some problems and explores the causes of the problems, and puts forward suggestions on how to strengthen the leading role of the government in urban social pension institutions in Hebei Province. It is not only of great significance to the construction of a service-oriented and responsible government in Hebei Province, but also conducive to improving the recognition of institutional elderly care, improving the quality of life of the elderly in Hebei Province, and enhancing the sense of happiness and gain of the elderly.